RELATIONSHIP BETWEEN ATTITUDE AND BEHAVIOR TOWARDS ENVIRONMENTAL SUSTAINABILITY - Mahat, Hanifah; Hashim, Mohmadisa; Saleh, Yazid; Nayan, Nasir; Suhaili, Samsudin; Balkhis Norkhaidi, Saiyidatina (International Journal of Psychosocial Rehabilitation, 2020)
This quantitative study explores the attitude-behavior gaps in young Malaysians’ environmental sustainability awareness. It involves 1,000 young Malaysians selected from five regional zones (north, central, south, east coast, and east Malaysia). A stratified random sampling technique based on age, gender, and location was used to select respondents. The study instrument was a questionnaire that involved two environmental sustainability awareness variables, comprising attitude and behavior. A descriptive analysis is used to represent level, frequency, and percentage. The level of the attitude and behavior variables was high. The relationship between the attitude and behavior variables and sub-variables reveals significantly moderate and weak relationships. There was no gap between attitude and behavior towards environmental sustainability awareness amongst young Malaysians. It is hoped that this study will provide the basis for further investigations into the levels of—and any gaps in—attitude and behavior towards environmental sustainability in Malaysian society and increase awareness of the issue.